Unconventional Means of Oil and Gas Production and Their Influence on International Trade - Černý, Martin; Štěrbová, Ludmila, 1957-; Baláž, Peter, 1954-2019; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The growing world population accompanied by an increase in GDP is effectively raising the demand for energy. One of the options are unconventional means of oil and gas, originating mainly from shales and oil sands. The goal of this thesis is to introduce the reader to unconventional means and their influence on international business. After a short introduction and definition an analysis of the situation in the U.S. follows, where the recent years have brought an increase in production from unconventional sources. The positive influence on the economy, employment and energetic security will be mentioned same as possible impacts on the environment. Furthermore the paper provides an analysis of the potential of repeating the U.S. shale revolution in other countries, with special focus on the EU. The success of unconventional sources opens the possibility of new trade routes, influence on the trade balance and the potential of influencing the whole gas market. However, it will also have an impact on current oil and gas producers. Considering the close bond between energetic security and politics, the thesis closes with an analysis of influences on the economy and politics of both -- current oil and gas producers and countries, which might be directly and indirectly affected by changes in the oil and gas market.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses